A Research Environment 2 km Deep-Underground Impacts Embryonic Development in Lake Whitefish (Coregonus clupeaformis) - Pirkkanen, Jake; Zarnke, Andrew M.; Laframboise, Taylor; Lees, Simon J.; Tai, T. C.; Boreham, Douglas R.; Thome, Christopher (Frontiers in Earth Science, 2020)
Biological research conducted in deep-underground environments is limited due to the lack of scientific infrastructure to accommodate the investigations, and only a few studies have utilized complex whole organism models. In this study, lake whitefish (Coregonus clupeaformis) embryogenesis was examined at two different developmental temperatures both at the Earth’s surface and within a research laboratory 2 km underground. Established developmental endpoints and morphometric analysis revealed significant differences between lake whitefish embryos reared in these two unique environments. These findings have been interpreted and discussed in the context of the novel research challenges faced in an inherently difficult to control deep-underground environment. This study represents one of the few investigations with an established whole organism model deep-underground and provides an opportunity to discuss the highly unique technical and logistical challenges of conducting biological experiments in this novel field of scientific research.